CHUDI (BANGLES), BINDI, AUR HIJAB WILL BRING ALONG INQUILAB (REVOLUTION): ANTI-PATRIARCHY WITHIN ANTI-FASCIST MOVEMENTS AND THE DESIRE FOR A NEW POLITICAL IN INDIA - Basu, Maitrayee (AoIR Selected Papers of Internet Research, 2020)
This paper looks at discursive interventions online and protests against political and social injustices against women in India within wider protests against the Citizenship Amendment Act (December 2019 - present). In attempting to classify some modes of publicness on digital media platforms that are prevalent amongst women resisting the oppressions of living under an authoritarian regime that overlaps with patriarchal structures, this paper explores the radical potential of spheres of affect that challenge representative authority and questions “who” has the right to construct the political. Drawing on theoretical approaches from Berlant (2008, 2011) and Fraser (2007, 2020), I discuss discourses emerging around women’s experiences whilst theorising the potential that feminist movements might possess to forge transnational solidarity. This paper employs digital ethnography on Twitter, as well as discourse analysis. Instead of utilising the more popular hashtag-analysis or keyword search methods used to study social movements and online cultures, I conduct a qualitative longitudinal analysis of user-timelines. In contrast to studies that measure the impact of digitally mediated activism, I highlight the work involved in constructing these transnational publics through an accurate prediction or ‘knowing’ of others within affective public spaces, as well as in strategic performances of belonging and citizenship.